Pocillopora aliciae: a new species of scleractinian coral (Scleractinia, Pocilloporidae) from subtropical Eastern Australia - Schmidt-Roach, Sebastian; Miller, Karen J.; Andreakis, Nikos (Zootaxa, 2013)
Lack of morphological features of diagnostic value and high levels of environmental phenotypic plasticity obscure species boundaries for most taxa in the genus Pocillopora Lamarck, 1816 and complicate the definition of taxonomically distinct units. Species of the genus are colonial, generally ramose, rarely massive or encrusting and mostly hermatypic; corallite arrangement is plocoid, septa are generally poorly developed and usually arranged in two cycles; the columella is mostly poorly developed (Veron & Pichon 1976). Verrucae are common, although reduced in some species. Currently 17 species are formally acknowledged within the genus (Veron 2000).